Studies on Biochemical Changes as an Indicator for Fracture Healing in Goats - Kumar, Dharmendra; Bhargava, Mahesh Kumar; Aparajita, Jahnawi; Shahi, Apra; Singh, Randhir (Indian Journal of Veterinary Sciences and Biotechnology, 2023)
Goats having long bone fracture brought to Teaching Veterinary Clinical Complex were included in present study. Biochemical attributes were recorded preoperatively and on 7th, 15th, 30th, 45th, 60th and 90th post- operative day after immobilizing the fracture segment with dynamic compression plate. An initial increase in values of alkaline phosphatase followed by its decrease till 60th day and again an increase up to 90th day was observed during fracture healing. Value of creatinine kinase showed a decreasing trend.  Gradual decrease in the values of serum calcium was observed till 45th post-operative day after which an elevation in this value was observed. Significant decrease in the values of serum phosphorous was observed on 7th post-operative day and this decrease continued till 90th post-operative day. The values of total protein increased gradually from 15th day onwards.  Values of blood glucose fluctuated within normal range. From the above discussion it could be concluded that biochemical parameters plays a pivotal role to ascertain the phase of fracture healing.
Keywords: Alkaline phosphatase; Blood glucose; Creatinine kinase; Fracture; Goat; Serum minerals